2021
DOI: 10.2186/jpr.jpr_d_20_00034
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of monolithic zirconia crowns: clinical behavior and survival rate at a 5-year follow-up

Abstract: Purpose: To evaluate the clinical behavior and survival of full coverage monolithic zirconia crowns on posterior teeth over a 5-year follow-up. Methods: Fifty patients were recruited and underwent restoration with a Lava Plus monolithic zirconia crown (Lava™ Frame Zirconia, 3M Espe, Germany) on premolars or molars. Patients were monitored over a 5-year follow-up (2014-19), recording any biological and/or mechanical complications; these data were used to estimate the crowns' success rate. Periodontal clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
4
27
1
1
Order By: Relevance
“…The literature contains only one clinical study conducted over a medium-term observation period. Rare technical complications with monolithic zirconia crowns were confirmed in this study by Solá-Ruiz et al Among 50 monolithic crowns fabricated from zirconia stabilized with 3-mol% yttrium oxide, only two decementations and one longitudinal fracture occurred over the observation period [16]. Sulaiman et al counted the frequency of remakes of monolithic restorations due to fracture over a 5-year period in two dental laboratories.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The literature contains only one clinical study conducted over a medium-term observation period. Rare technical complications with monolithic zirconia crowns were confirmed in this study by Solá-Ruiz et al Among 50 monolithic crowns fabricated from zirconia stabilized with 3-mol% yttrium oxide, only two decementations and one longitudinal fracture occurred over the observation period [16]. Sulaiman et al counted the frequency of remakes of monolithic restorations due to fracture over a 5-year period in two dental laboratories.…”
Section: Discussionsupporting
confidence: 67%
“…The dentists were somewhat more critical than the patients themselves. For patients, it seems to be more important that their restoration(s) are unaffected by complications [16] rather than that the tooth shade is 100% consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Debonding was the most noted complication for full-coverage 3% Y-TZP monolithic posterior crowns in a 5-year prospective study. 33 This study showed that all three ceramic endocrowns bonded to tooth structure provided an adequate coronal seal that enabled at least partial healing of periapical lesions within the two-year observation period. 34 In the lithium disilicate group, one tooth developed a new periapical lesion.…”
Section: Discussionmentioning
confidence: 64%
“…There is a substantial increase in the use of zirconia (Zr) dental restorations in the recent years [ 1 ] due to the excellent biocompatibility, superior mechanical properties (such as high fracture strength/fracture toughness) and physical properties (dimensional stability, color matching with the teeth and sufficient precision) for dental applications [ 2 ]. The use of Zr ceramics is not limited to the single crowns and used for the fabrication of endodontic posts, fixed partial dentures (FPD), implant abutments and frameworks [ 3 , 4 ]. The brittle nature of ceramic leading to the formation of inherent defects and microcracks remain the main obstacle for using the metal-free ceramic restorations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%